Pengaruh Pembelajaran Daring Learning Management System (LMS), Multimedia dan Motivasi Belajar Terhadap Kemampuan Pemahaman Membaca Peserta Didik - Dwi Nur Jayanti; Retno Danu Rusmawati; Hartono Hartono (Departement of Mathematics Education, 2023)
This study has the objectives: (1) to determine the effect of online learning management system (LMS) with multimedia on student motivation, (2) to determine the effect of online learning management system (LMS) with multimedia on students' reading comprehension ability, (3) To find out the effect of motivation on students' reading comprehension ability, and (4) To find out the interaction between online learning management system (LMS) learning with multimedia and learning motivation on students' reading ability. This study uses an experimental design which is divided into two classes, namely online learning management system (LMS) with multimedia and online learning management system (LMS) without multimedia where in the data analysis technique process used is 2-way analysis of Variance (Anava). The population of this study was students of class IV with the research sample being students of class IVA and class IVB which totaled 72 students. Based on the results of calculations with Anava, it is obtained FA count > F table (8.292 > 4.02) which explains that online learning management system (LMS) learning with multimedia has a significant effect on students' reading comprehension ability; FB count > F table (9.871 > 4.02) which explains that motivation has a significant effect on students' reading comprehension ability; and FAB count > F table (4.787 > 4.02), which explains that there is an interaction between online learning management system (LMS) learning and multimedia and learning motivation on students' reading abilities.